(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The primary aim of this article is to propose a method for teaching English in mixed-ability classrooms, based on personal teaching practice. This method focuses on a simultaneous focus on both the syntagmatic and paradigmatic relations of language. Although memorizing long lists of new words and learning grammatical rules can be tedious, they are essential components of language learning. With a limited amount of time available for learners to grasp these concepts, reading texts are divided into syntagms at the phrasal level to facilitate learning. As a pre-reading activity, students receive lists of these syntagms along with their meanings in their native language. making use of the native language helps create a supportive environment where students can build self-esteem while engaging with the foreign language. This list is reviewed and partially memorized in a session to ensure that students are comfortable with pronunciation and grammatical relations within segments. The teacher’s personality plays an important role in this process, as the human element is central to all linguistic activities.